MIR106A-5p upregulation suppresses autophagy and accelerates malignant phenotype in nasopharyngeal carcinoma. Issue 7 (3rd July 2021) - Zhu, Qingwen; Zhang, Qicheng; Gu, Miao; Zhang, Kaiwen; Xia, Tian; Zhang, Siyu; Chen, Wenhui; Yin, Haimeng; Yao, Hui; Fan, Yue; Pan, Si; Xie, Haijing; et al.
ABSTRACT: Dysregulated microRNAs (miRNAs) are involved in carcinoma progression, metastasis, and poor prognosis. We demonstrated that in nasopharyngeal carcinoma (NPC), transactivated MIR106A-5p promotes a malignant phenotype by functioning as a macroautophagy/autophagy suppressor by targeting BTG3 (BTG anti-proliferation factor 3) and activating autophagy-regulating MAPK signaling. MIR106A-5p expression was markedly increased in NPC cases based on quantitative real-time PCR, miRNA microarray, and TCGA database analysis findings. Moreover, MIR106A-5p was correlated with advanced stage, recurrence, and poor clinical outcomes in NPC patients. In addition to three-dimensional cell culture assays, zebrafish and BALB/c mouse tumor models revealed that overexpressed MIR106A-5p targeted BTG3 and accelerated the NPC malignant phenotype by inhibiting autophagy. BTG3 promoted autophagy, and its expression was correlated with poor prognosis in NPC. Attenuation of autophagy, mediated by the MIR106A-5p -BTG3 axis, occurred because of MAPK pathway activation. MIR106A-5p overexpression in NPC was due to increased transactivation by EGR1 and SOX9. Our findings may lead to novel insights into the pathogenesis of NPC. Abbreviations: ACTB: actin beta; ATG: autophagy-related; ATG5: autophagy related 5; BLI: bioluminescence; BTG3: BTG anti-proliferation factor 3; CASP3: caspase 3; ChIP: chromatin immunoprecipitation; CQ: chloroquine; Ct: threshold cycle; DAPI: 4ʹ, 6-diamidino-2-phenylindole; DiL: 1, 1ʹ-dioctadecyl-3, 3, 3ʹ, 3ʹ-tetramethylindocarbocyanine perchlorate; EBSS: Earle's balanced salt solution; EGR1: early growth response 1; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GEO: Gene Expression Omnibus; GFP: green fluorescent protein; IF: immunofluorescence; IHC: immunohistochemistry; ISH: in situ hybridization; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; MIR106A-5p: microRNA 106a-5p; miRNAs: microRNAs; MKI67: marker of proliferation ki-67; mRNA: messenger RNA; MTOR: mechanistic target of rapamycin kinase; NPC: nasopharyngeal carcinoma; qRT-PCR: quantitative real-time PCR; siRNA: small interfering RNA; SOX9: SRY-box transcription factor 9; SQSTM1: sequestosome 1; TCGA: The Cancer Genome Atlas; WB: western blot.